Thiamine prescribing practices within university‐affiliated hospitals: A multicenter retrospective review. Issue 4 (3rd February 2015) - Day, Gregory S.; Ladak, Safiya; Curley, Kevin; Farb, Norman A. S.; Masiowski, Paul; Pringsheim, Tamara; Ritchie, Michael; Cheung, Alexandra; Jansen, Sandy; Methot, Linda; Neville, Heather L.; Bates, Duane; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Patients with suspected thiamine deficiency should receive treatment with parenteral thiamine to achieve the high serum thiamine levels necessary to reverse the effects of deficiency and to circumvent problems with absorption common in the medically ill. OBJECTIVE To quantify rates of parenteral administration of thiamine across university‐affiliated hospitals and to identify factors associated with higher rates of parenteral prescribing. DESIGN Multicenter, retrospective observational study of thiamine prescriptions. METHODS Prescriptions for thiamine were captured from computerized pharmacy information systems across participating centers, providing information concerning dose, route, frequency, and duration of thiamine prescribed from January 2010 to December 2011. SETTING Fourteen university‐affiliated tertiary care hospitals geographically distributed across Canada, including 48, 806 prescriptions for thiamine provided to 32, 213 hospitalized patients. RESULTS Parenteral thiamine accounted for a statistically significant majority of thiamine prescriptions (57.6%, P < 0.001); however, oral thiamine constituted a significant majority of the total doses prescribed (68.4%, z = 168.9; P < 0.001). Protocols prioritizing parenteral administration were associated with higher rates of parenteral prescribing (61.3% with protocol, 45.8% without protocol; P < 0.001). Patients admitted under psychiatry services were significantly more likely to be prescribed oral thiamine (P < 0.001). CONCLUSIONS Although parenteral thiamine accounted for a statistically significant majority of prescriptions, oral thiamine was commonly prescribed within academic hospitals. Additional strategies are needed to promote parenteral thiamine prescribing to patients with suspected thiamine deficiency. Journal of Hospital Medicine 2015;10:246–253. © 2015 Society of Hospital Medicine